(untitled) (World Science, 2021)
The article addresses the problems of the evaluation methodology improvement of the transport service efficiency and quality provided to passengers on suburban bus routes in accordance with the modern management system requirements. The purpose of the study is to provide practical recommendations to motor transport enterprises following which they can improve the level of service provided to suburban bus route passengers, as well as to provide a structured approach that will allow transport organizations to respond objectively and reasonably to requests resulting from new passenger transportation needs. For a comprehensive assessment of quantitative and qualitative transport service indicators, the evaluation method of the transport service efficiency is proposed. This approach makes it possible to reflect the transport service level both through the prism of enterprises` operation efficiency and the quality of transport service provision. The results of the study are of practical importance in the application of such methods in motor transport enterprises` activity providing the necessary information for management in modern business conditions.